277 Can intensively managed cows improve efficiency of converting human-inedible feedstuffs to high-quality human edible food?. (7th December 2018) - Wickersham, T
Abstract: Upcycling of protein by cattle, that is, production of a high-quality human-edible protein from sources of low biological value, is dependent on all sectors of the value chain being individually sustainable while optimizing use of human-edible nutrients. Exclusive reliance on ranch-raised forages (endogenous calories) exposes individual cow/calf producers to significant risk, including economic risks and degradation of the ecological system. Reduced forage availability across an entire region caused by alternative land uses or significant weather events challenges all three attributes of sustainable beef production. Intensification, accomplished by partial or complete confinement, creates opportunities to enhance the economic, environmental, and social sustainability of beef cattle production. Intensification of cow/calf systems is dependent on exogenous calories being purchased and delivered using feedstuffs and feeding methods not typically utilized by grazing cattle. Limit feeding during gestation has consistently decreased maintenance requirements and reduced feed usage without compromising system performance. Increasing energy density may decrease feed delivery costs, reduce methane production, and decrease manure production. Limit feeding as an alternative to ad libitum hay feeding decreased costs and increased the likelihood of profitability while minimizing risk to producers. While intensification would seem most feasible for large scale producers, through careful management smaller producers without access to feed handling equipment can take advantage of intensification. Intensification potentially shifts the cow's diet to rely more on human-edible feedstuffs; however, incorporation of by-products from other industries reduces this shift. A concomitant reduction in methane production with intensification of cow/calf systems provides an additional benefit both in energy available to cow and a reduced environmental footprint. Intensification, managed correctly, enhances the sustainability of beef production.